Pismis 20: One or two clusters? - Orsatti, Ana María (2003)
We present UBVRI polarimetric observations of stars in the direction of the open cluster Pismis 20 and WR 67. It is found that the observed members segregate polarimetrically into two groups, with different associated mean Pmax (4.31 and 6.08% respectively). Although in the literature these stars are considered as members of the same cluster, the polarized light from these groups clearly differs. There are two possible explanations: very efficient polarizing dust particles exists between certain members of the cluster; or else Pismis 20 is composed of different groupings superimposed along the line of sight. WR 67 belongs to the group more affected by the dust.